Combining genome-wide and transcriptome-wide analyses reveal the evolutionary conservation and functional diversity of aquaporins in cotton - Li, Weixi (BMC Genomics, 2019)
BACKGROUND: Aquaporins (AQPs) are integral membrane proteins from a larger family of major intrinsic proteins (MIPs) and function in a huge variety of processes such as water transport, plant growth and stress response. The availability of the whole-genome data of different cotton species allows us to study systematic evolution and function of cotton AQPs on a genome-wide level. RESULTS: Here, a total of 53, 58, 113 and 111 AQP genes were identified in G. arboreum, G. raimondii, G. hirsutum and G. barbadense, respectively. A comprehensive analysis of cotton AQPs, involved in exon/intron structure, functional domains, phylogenetic relationships and gene duplications, divided these AQPs into five subfamilies (PIP, NIP, SIP, TIP and XIP). Comparative genome analysis among 30 species from algae to angiosperm as well as common tandem duplication events in 24 well-studied plants further revealed the evolutionary conservation of AQP family in the organism kingdom. Combining transcriptome analysis and Quantitative Real-time PCR (qRT-PCR) verification, most AQPs exhibited tissue-specific expression patterns both in G. raimondii and G. hirsutum. Meanwhile, a bias of time to peak expression of several AQPs was also detected after treating G. davidsonii and G. hirsutum with 200 mM NaCl. It is interesting that both PIP1;4 h/i/j and PIP2;2a/e showed the highly conserved tandem structure, but differentially contributed to tissue development and stress response in different cotton species. CONCLUSIONS: These results demonstrated that cotton AQPs were structural conservation while experienced the functional differentiation during the process of evolution and domestication. This study will further broaden our insights into the evolution and functional elucidation of AQP gene family in cotton. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-019-5928-2) contains supplementary material, which is available to authorized users.